Compressed earth blocks (CEB) compression tested under two earth standards. Issue 1 (31st December 2023) - Aranda-Jiménez, Yolanda; Zuñiga-Leal, Carlos; Moreno-Chimely, Laura; Robles-Aranda, María Emilia
Abstract: Building with raw earth is a responsibility that translates into safe, low-impact and small carbon footprint constructions. However, beyond its current use, it is imperative to validate the different earth construction systems, starting with their components, under standards that ensure the safety of this type of constructions. In countries where construction with earth is allowed, it is verified by Standards and Technical Documents or Construction Regulations. Therefore, the objective of the research is to contrast a series of compressed earth blocks (CEB) subjected to compression tests with the Brazilian and Colombian standards, and the Mexican standards with clay soils in the region, identifying the deviations between the results and their possible causes. In the results, it was observed that the compression test procedure varies for each Standard, the Brazilian and Colombian Standards being similar, and these in turn adhere more to the construction system, while with the Mexican Standard the results are higher than the previous one since the norm requires to test the complete block.